2019
DOI: 10.1186/s12904-019-0411-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences of nurse-facilitated advance care planning in a general practice setting: a qualitative study

Abstract: Background Advance care planning (ACP) can offer benefits to patients and their families, especially when delivered in outpatient settings, but uptake remains low. Common barriers for health professionals include a perceived lack of time and adequate training, experience, and confidence in conducting ACP. Patient-reported barriers include a lack of awareness of ACP or discomfort initiating or engaging in discussions about end-of-life. Methods We aimed to explore patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 22 publications
(44 reference statements)
5
73
0
Order By: Relevance
“…When considering barriers to ACP in general practice from an individual perspective, there were very few general practice studies directly involving patients 14 39–43. A few studies described patient experience by proxy through opinions obtained from GPs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When considering barriers to ACP in general practice from an individual perspective, there were very few general practice studies directly involving patients 14 39–43. A few studies described patient experience by proxy through opinions obtained from GPs.…”
Section: Resultsmentioning
confidence: 99%
“…Attitudes of individuals about ACP were reported to vary widely. Studies reported the perceived irrelevance of ACP was a barrier, with the relevance of ACP described with ambivalence when associated with an existing state of wellness or absence of terminal diagnoses 13 14…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…59 Once barriers are overcome, GPNs can play a beneficial role in undertaking advanced care planning. 60 GPNs already play a significant role in co-ordinating and working with multidisciplinary teams, and providing support for people with advanced chronic disease and frailty. [61][62][63][64] An expanding role for GPNs to be involved in ACP is being explored.…”
Section: Comparision With the Literaturementioning
confidence: 99%